2% Crisaborole topical ointment for the treatment of mild-to-moderate atopic dermatitis. (4th May 2017) - Cheape, Alice C.; Murrell, Dedee F.
ABSTRACT: Introduction : Crisaborole 2% topical ointment is an anti-inflammatory, non-steroidal phosphodiesterase 4 inhibitor which is currently under investigation for its potential role in the treatment of atopic dermatitis and psoriasis. Areas covered : So far, 7 trials have been completed in atopic dermatitis. The 2% strength appeared to be the superior dosing regimen. Pruritus improved significantly within one week. The improvements in objective efficacy assessments in crisaborole-treated patients were also statistically significant compared to the vehicle. Expert commentary : Crisaborole has several key features in its mode of action which distinguish it from existing treatments for atopic dermatitis (AD), notably its activity against the phosphodiesterase E4 (PDE4) pathway, regulating cyclic AMP (cAMP) levels. This is less immunosuppressive than other pathways and has no effect on skin thinning. The pathway interrupts the itch sensation (pruritus) which means that the itch-scratch cycle, the bane in the life of patients with AD, is interrupted, usually as early as a few days into treatment. Hence, with the promising safety profile demonstrated, early treatment of mild to moderate AD patients might help to control AD better and improve quality of life for patients.